اشكاليات الطريقة الانتخابية في قانون انتخاب اعضاء مجلس النواب ومجالس المحافظات والاقضية رقم (4) لعام 2023 - الجعيفري, زهراء فاهم حسن; الصراف, صلاح حسن حمود (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Electoral reform is an integral part of the comprhensive reform process in iraq at all levels, as a result of the urgent need to researah the problems of the iraqi saint-lego method, and work to provide solutionns and proposals to addrss the method in order to support the modern political process in iraq. This is part of the researah assumes the Electoral mothed is part of the Electoral process and is a subuent stage of the voting process, and that the Electoral mothed is concerned with extracting the results of the ballot and knowing the winners of the Elections. Also, the Electoral mothed (saint-lego) applied in the Iraqi council of Representatives Elections for the years 2014 and 2018 did not lead to fair and satisfactory results for the Iraqi street.